Specificity of the ModA11, ModA12 and ModD1 epigenetic regulator N6-adenine DNA methyltransferases of Neisseria meningitidis. Issue 8 (6th April 2015) - Seib, Kate L.; Jen, Freda E.-C.; Tan, Aimee; Scott, Adeana L.; Kumar, Ritesh; Power, Peter M.; Chen, Li-Tzu; Wu, Hsing-Ju; Wang, Andrew H.-J.; Hill, Dorothea M. C.; Luyten, Yvette A.; Morgan, Richard D.; et al.
Abstract : Phase variation (random ON/OFF switching) of gene expression is a common feature of host-adapted pathogenic bacteria. Phase variably expressed N 6 -adenine DNA methyltransferases (Mod) alter global methylation patterns resulting in changes in gene expression. These systems constitute phase variable regulons called phasevarions. Neisseria meningitidis phasevarions regulate genes including virulence factors and vaccine candidates, and alter phenotypes including antibiotic resistance. The target site recognized by these Type III N 6 -adenine DNA methyltransferases is not known. Single molecule, real-time (SMRT) methylome analysis was used to identify the recognition site for three key N. meningitidis methyltransferases: ModA11 (exemplified by M.NmeMC58I) (5′-CGY m6 A G-3′), ModA12 (exemplified by M.Nme77I, M.Nme18I and M.Nme579II) (5′-AC m6 A CC-3′) and ModD1 (exemplified by M.Nme579I) (5′-CC m6 A GC-3′). Restriction inhibition assays and mutagenesis confirmed the SMRT methylome analysis. The ModA11 site is complex and atypical and is dependent on the type of pyrimidine at the central position, in combination with the bases flanking the core recognition sequence 5′-CGY m6 A G-3′. The observed efficiency of methylation in the modA11 strain (MC58) genome ranged from 4.6% at 5′-GCGC m6 A GG-3′ sites, to 100% at 5′-ACGT m6 A GG-3′ sites. Analysis of the distribution of modified sites in the respective genomes shows many cases of association with intergenic regions of genes with altered expression due to phasevarion switching.